Kidney, limb and ophthalmic complications and death in patients with nonvalvular atrial fibrillation and type 2 diabetes prescribed rivaroxaban or warfarin: an electronic health record analysis. (24th May 2021) - Costa, O; Brescia, CW; Vardar, B; Abdelgawwad, K; Sood, N; Coleman, CI
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Bayer AG, Berlin, Germany INTRODUCTION: Patients with nonvalvular atrial fibrillation (NVAF) and type 2 diabetes (T2D) have a higher risk of kidney, limb, and ophthalmic complications than those without T2D. PURPOSE: We sought to evaluate these complications and death in patients with NVAF and T2D prescribed rivaroxaban or warfarin. METHODS: We analyzed Optum® de-Identified electronic health record (EHR) data from 11/2010-12/2019. We included adults with NVAF and T2D newly initiated on rivaroxaban or warfarin with ≥12 months of prior EHR activity. Patients with another indication for anticoagulation, valve disease, history of end-stage renal disease, major adverse limb events (MALE), diabetic retinopathy or pregnancy were excluded. We evaluated the incidence rate of developing a composite outcome of >40% decrease in estimated glomerular filtration incidence rate (eGFR) from baseline, eGFR < 15 mL/minute/1.73 m2, need for dialysis or kidney transplant, MALE, diabetic retinopathy or death. Overlap weighting was used to balance baseline characteristics between cohorts while preserving sample size.  Hazard ratios with 95% confidence intervals were calculated using propensity score-overlap weighted Cox regression. RESULTS: We included 24912 rivaroxaban and 58270 warfarin users. Rivaroxaban was associated with a significant reduction in the composite endpoint versus warfarin (-19.7 events per 1000 person years) driven mostly by an >40% decrease in eGFR from baseline, need for dialysis or renal transplant, MALE and death (Figure 1). CONCLUSIONS: Rivaroxaban was associated with reduced incidence rates of kidney and limb complications, and death in NVAF patients with T2D. FUNDING:  Funding for this study was provided by Bayer AG, Berlin, Germany